The Effect of Methanol-Blended Fuel on Fuel Consumption and Exhaust Emissions of a 150 cc Gasoline Motorcycle - Mochammad Miftachul Syanusi; Hadromi; Rizqi Fitri Naryanto; Ranu Iskandar (JMEL : Journal of Mechanical Engineering Learning, 2025)
This study aims to determine the effect of methanol-blended fuel variations on fuel consumption and exhaust emissions Honda Supra X125 FI. The background of this research is the need for environmentally friendly and efficient alternative fuels to reduce air pollution from motorized vehicles. Methanol was chosen as an additive due to its high octane number and oxygen content in its structure, which can improve combustion efficiency. The tests were conducted using a Honda Supra X125 FI motorcycle with five fuel mixture variations: 0%, 5%, 10%, 15%, and 20% methanol in Shell V-Power. Data were collected using a gas aalyzer and a dynamometer to measure fuel consumption and CO and HC emission levels. The results show that methanol addition increases fuel consumption by up to 17.99% in the 20% methanol mixture due to methanol's lower calorific value compared to gasoline. However, CO emissions decreased by 23% and HC emissions by 19.26%. The 10% methanol mixture is optimal as it balances combustion efficiency and fuel consumption. The findings indicate that methanol has potential as a fuel additive for reducing emissions in gasoline motorcycles, although higher methanol concentrations may increase fuel consumption.